Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
Volume 3: Design and Manufacturing 2007
DOI: 10.1115/imece2007-44007
|View full text |Cite
|
Sign up to set email alerts
|

Design and Analysis of Ultrasonic Assisted Friction Stir Welding

Abstract: This paper presents ultrasonic assisted friction stir welding (UaFSW), which is suggested to improve the weld quality and efficiency as a hybrid welding system. Ultrasonic-assisted processes have been coupled with tooling in various manufacturing processes to enhance the performance of conventional machining and bonding processes. For successful and effective implementation of the UaFSW, we must first consider how to integrate ultrasonics into the friction stir welding equipment. To solve this problem, we desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
57
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 0 publications
1
57
0
1
Order By: Relevance
“…On the other hand, lateral moving force F x increased rapidly but after certain period of fluctuations also reached to a stable state. Compared with the works of Trimble et al [21], Soundararajan et al [22], and Park [23] where similar aluminum alloys were friction stir welded, three differences in the force curves can be observed. First, only one peak axial force existed during the plunge stage for welding dissimilar materials, whereas two peaks occurred for welding same aluminum alloy.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…On the other hand, lateral moving force F x increased rapidly but after certain period of fluctuations also reached to a stable state. Compared with the works of Trimble et al [21], Soundararajan et al [22], and Park [23] where similar aluminum alloys were friction stir welded, three differences in the force curves can be observed. First, only one peak axial force existed during the plunge stage for welding dissimilar materials, whereas two peaks occurred for welding same aluminum alloy.…”
Section: Resultsmentioning
confidence: 69%
“…Peak axial force was generated as the tool shoulder abraded against steel surface. Second, when welding similar aluminum alloys, axial force F z can be greatly reduced by 35-60% [21,23] during welding stage whereas no more than 20% reduction can be observed when welding Al to TRIP steel. Finally, lateral moving force F x , which is the forced required for translating FSW tool along weld line, was negligible when welding aluminum.…”
Section: Resultsmentioning
confidence: 95%
“…Roylin et al [6] studied FSP temperature in presence and absence of ultrasonic vibrations for aluminum 2024. Their findings indicated that temperature of the stirred zone in both simple and ultrasonic-assisted FSP was almost the same, and ultrasonic vibrations did not significantly affect temperature of the stirred zone in lower traverse speed (150 mm/min).…”
Section: Visual Inspection Of Fabricated Nano-compositesmentioning
confidence: 99%
“…Heretofore, the literature contains little information about the UAFSW and UAFSP of polymers. Park [5,6] studied the effect of ultrasonic vibration on FSW of Al 6061. He introduced ultrasonic vibration to the workpiece through FSW tool and in its traverse direction.…”
mentioning
confidence: 99%
“…According to their results, transverse tensile strength can reach 93% of the base aluminum alloy and the joint elongation can be significantly increased with a ductile fracture mode. Park (2009) developed an ultrasonic assisted FSW process and reported that ultrasonic vibration can help eliminate the wormhole defect at the weld root. Grant et al (2005) implemented an induction heating system in front of the FSW tool and obtained great reduction of loadings on the tool.…”
Section: Introductionmentioning
confidence: 99%